An 'inside-out' perspective on managing information in new product development. (4th December 2006) - Frishammar, Johan; Chroneer, Diana
A continuous stream of books and papers has suggested that firms need to apprehend information about environmental factors such as customers, competitors and new technologies in order to enable effective New Product Development (NPD). Often, this literature takes an 'outside-in' perspective, and argues that firms need to utilise tools such as industry structure analysis and the OT component of SWOT to increase NPD performance. This paper outlines an alternative 'inside-out' perspective, and suggests that firms should start not by focusing on the environment, but rather on their resources and capability for managing information. The paper develops and explicates a three-component capability of managing information in NPD. The paper concludes with managerial implications by pointing to a variety of techniques and tools that management and other practitioners involved with NPD can use to build and sustain the capability of managing information.